On using the Stroboconn - Jones, A. M. (International Library of African Music, 1970)
Though most research workers are nowadays familiar with the Stroboconn, it is time that an assessment should be made of the best way of using it in the field of African music. For the benefit of the uninitiated, we start with a brief description. The Stroboconn is an apparatus for measuring the pitch of notes, either sung or played: this it does to an accuracy of one hundredth of a semitone (= 1 cent). It consists of twelve stroboscopes, one for each semitone of an octave tuned in equal temperament, that is, our western chromatic scale, with a basic pitch of A = 440 v.p.s.
Keywords: Ethnomusicology; Tuning; Musical instruments; Musical pitch; Measurement; Africa; African Music